2011
DOI: 10.1016/j.yexcr.2011.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Identification of T-cell factor-4 isoforms that contribute to the malignant phenotype of hepatocellular carcinoma cells

Abstract: The Wnt/β-catenin signaling pathway is frequently activated in hepatocellular carcinoma (HCC). Downstream signaling events involving the Wnt/β-catenin cascade occur through T-cell factor (TCF) proteins. The human TCF-4 gene is composed of 17 exons with multiple alternative splicing sites. However, the role of different TCF-4 isoforms in the pathogenesis of HCC is unknown. The purpose of this study was to identify and characterize TCF-4 isoforms in HCC. We identified 14 novel TCF-4 isoforms from four HCC cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
80
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(86 citation statements)
references
References 33 publications
(31 reference statements)
5
80
1
Order By: Relevance
“…Therefore, we supposed that TCF-4K might regulate relevant target genes like C-myc to affect cell proliferation. In contrast to the conclusions of Tsedensodnom et al (2011) from their research on hepatoma carcinoma cells, we found that over-expression of TCF-4K could significantly inhibit the migration of A549 cells, which might be caused by the down-regulation of migration-relevant target genes. Therefore, our data indicate that TCF-4K might function as tumor suppressor in NSCLC by down-regulating the Wnt pathway.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Therefore, we supposed that TCF-4K might regulate relevant target genes like C-myc to affect cell proliferation. In contrast to the conclusions of Tsedensodnom et al (2011) from their research on hepatoma carcinoma cells, we found that over-expression of TCF-4K could significantly inhibit the migration of A549 cells, which might be caused by the down-regulation of migration-relevant target genes. Therefore, our data indicate that TCF-4K might function as tumor suppressor in NSCLC by down-regulating the Wnt pathway.…”
Section: Discussioncontrasting
confidence: 99%
“…Sequence analysis was performed using the NCBI nucleotide blast web service, and validated that the 1700 bp band that was missing in lung cancer cells represented an alternative splicing isoform of TCF-4. This isoform had also been previously identified as an inhibitory transcriptional factor of the Wnt pathway in hepatocellular carcinoma cell lines (Tsedensodnom et al, 2011). The TCF4 gene includes five essential domains for transcription function: an N-terminal β-catenin-binding domain (BCBD, exon 1), a Groucho-related-gene (Grg)/ transducin-like enhancer of split (TLE) transcriptional corepressor binding site (exons 9 and 10), a high mobility-group-box (HMG-box) DNA-binding domain (exons 10 and 11), an adjacent nuclear localization signal (NLS, exon 12), and a C-terminal binding protein binding site (CtBP, exon 17).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Original studies in Xenopus systems showed that forms with SxxSS behave like repressors, whereas forms missing this motif act like activators (Liu et al 2005). This was recently confirmed in a study of human hepatocellular carcinoma in which of the 14 alternatively spliced TCF4 isoforms expressed in liver cancer cells, those that contained the SxxSS motif were growth suppressive, whereas those lacking the element were Wnt activating and growth promoting (Tsedensodnom et al 2011). The fact that SxxSS forms of TCF4 are generated through alternative splicing means that the prevalence of these forms could differ among cell types and cell stages.…”
Section: Tcf/lef Heterogeneitymentioning
confidence: 86%